Effect of High-Intensity Interval Training in De Novo Heart Transplant Recipients in Scandinavia: One-Year Follow-Up of the HITTS Randomized, Controlled Study. Issue 19 (7th May 2019) - Nytrøen, Kari; Rolid, Katrine; Andreassen, Arne Kristian; Yardley, Marianne; Gude, Einar; Dahle, Dag Olav; Bjørkelund, Elisabeth; Relbo Authen, Anne; Grov, Ingelin; Philip Wigh, Julia; Have Dall, Christian; Gustafsson, Finn; et al.
Abstract : Background: There is no consensus on how, when, or at what intensity exercise should be performed after heart transplantation (HTx). We have recently shown that high-intensity interval training (HIT) is safe, well tolerated, and efficacious in the maintenance state after HTx, but studies have not investigated HIT effects in the de novo HTx state. We hypothesized that HIT could be introduced early after HTx and that it could lead to clinically meaningful increases in exercise capacity and health-related quality of life. Methods: This multicenter, prospective, randomized, controlled trial included 81 patients a mean of 11 weeks (range, 7–16 weeks) after an HTx. Patients were randomized 1:1 to 9 months of either HIT (4×4-minute intervals at 85%–95% of peak effort) or moderate-intensity continuous training (60%–80% of peak effort). The primary outcome was the effect of HIT versus moderate-intensity continuous training on the change in aerobic exercise capacity, assessed as the peak oxygen consumption (VO2 peak). Secondary outcomes included tolerability, safety, adverse events, isokinetic muscular strength, body composition, health-related quality of life, left ventricular function, hemodynamics, endothelial function, and biomarkers. Results: From baseline to follow-up, 96% of patients completed the study. There were no serious exercise-related adverse events. The population comprised 73% men, and the mean±SD age was 49±13 years. At the 1-year follow-up, the HIT group demonstrated greater improvements than the moderate-intensity continuous training group; the groups showed significantly different changes in the VO2 peak (mean difference between groups, 1.8 mL·kg − 1·min − 1), the anaerobic threshold (0.28 L/min), the peak expiratory flow (11%), and the extensor muscle exercise capacity (464 J). The 1.8-mL·kg − 1·min − 1 difference was equal to ≈0.5 metabolic equivalents, which is regarded as clinically meaningful and relevant. Health-related quality of life was similar between the groups, as indicated by results from the Short Form-36 (version 2), Hospital Anxiety and Depression Scale, and a visual analog scale. Conclusions: We demonstrated that HIT was a safe, efficient exercise method in de novo HTx recipients. HIT, compared with moderate-intensity continuous training, resulted in a clinically significantly greater change in exercise capacity based on the VO2 peak values (25% versus 15%), anaerobic threshold, peak expiratory flow, and muscular exercise capacity. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier NCT01796379. Abstract : Supplemental Digital Content is available in the text.